Analisa Daya Minat Karyawan Industri Melanjutkan ke Program Magister Teknik: Studi Kasus Industri Manufaktur Cilegon - Anton Irawan; Sjaifuddin Sjaifuddin; Indar Kustingsih; Teguh Kurniawan (Tirtayasa Ekonomika, 2020)
Chemical Engineering was one of the fields of engineering to process raw materials into more useful materials. Starting in beginning of 2019, Sultan Ageng Tirtayasa University (UNTIRTA) has a Chemical Engineering postgraduate program based on SK Menristekdikti No. 88 / KPT / I / 2019. Based on this permit, the postgraduate program has a chemical engineering study program and the next was to get as many Untirta chemical engineering graduate students. Untirta postgraduate chemical engineering students can come from undergraduate students who have just completed bachelor or graduate level lectures who have worked in industry, business or government. It is not yet known specialization of prospective graduate students from new graduates or persons who are already working so it is necessary to conduct a test of specialization of prospective students to the chemical engineering study program Untirta                      post-graduation. An interest test was obtained by research conducted through the process of distributing questionnaires and interviews to prospective graduate students. The purpose of this study is to obtain data of interest from chemical engineering graduates in Banten Province to proceed to the Untirta chemical engineering postgraduate study program which will be useful to maximize getting as many students as possible to the Untirta chemical engineering graduate program. The initial stage of this research is a comparative study with other universities that already have a postgraduate program in Chemical Engineering. The choice is to go to the Muslim University of Indonesia (UMI) because UMI has a relatively large number of postgraduate courses with not many locations in the Chemical Industry. The results of the analysis of respondents that respondents from high school / vocational teachers need to be facilitated to strengthen the knowledge of vocational school teachers in the field of Industrial Chemistry. The interest of prospective Masters students in Chemical Engineering Untirta can be increased through the promotion path to the HRD at work as well as intensive promotion through social media channels. Cost constraints can be found solutions through project scholarships from industry. Information technology will be a solution in solving the problem of distance and time in attending lectures in the Chemical Engineering Untirta.